A new rejuvenation heat treatment of crept Ni-based superalloy single crystals. Issue 1 (1st July 2022) - Lin, Sicong; Shen, Hao; Zhou, Guangni; He, Weifeng; Chen, Kai
Abstract: Ni-based superalloys are widely used in harsh environments due to their exceptional high-temperature mechanical properties, and their microstructures are inevitably subjected to degradation, including accumulation of strain/stress, generation of high density of dislocations, and rafting of γ′-particles, under creep damage. To prolong their service life, rejuvenation heat treatment is proposed to restore their microstructure. In this study, a Ni-based superalloy single crystal specimen with 0.15% creep strain is taken as a surrogate of partially served components. The microstructure, including the dislocation density and distribution as well as the size and morphology of γ′-particles, is investigated. Then two comparative heat treatment protocols are applied to the crept superalloy single crystal. Because super-solvus homogenization treatment triggers recrystallization, a recovery pre-annealing step at sub-solvus temperature is designed to relieve the stored deformation energy. After homogenization and aging heat treatment, the single crystalline structure is preserved, and in the meanwhile the γ′-particles are restored to uniform cuboidal morphology and the dislocations are fully eliminated. Our findings provide a route to rejuvenate crept superalloy single crystals.